The first geophytic Lobivia (Cactaceae) - Kiesling, Roberto (2001)
Lobivia bonniae was described recently in a publication of a Czech museum (Halda and Horácek, 1999) and was also featured in a hobbyist Czech magazine (Halda and Janeba, 1999). As these publications may be difficult for many readers to obtain, the following information is presented. This species originates from the Argentine province of Catamarca, in the mountains around Fiambalá.  It is closely related to L. famatimensis, but the tuberous roots -- a unique, hitherto unrecorded character for the genus --  as well the cylindrical stems differentiate it from this well-known species.  This is not only the first lobivia with tuberous roots but also the only known member of the genus with stems that are eventually deciduous. Geophytism is a frequent adaptation of plants in arid zones but relatively rare in Cactaceae and previously unknown in Lobivia and related genera.